Echocardiographic parameters associated with pulmonary congestion in outpatients with Chagas' cardiomyopathy and non-chagasic cardiomyopathy - Barral,Marselha Marques (2012)
INTRODUCTION: Despite significant left ventricular (LV) systolic dysfunction and cardiomegaly, pulmonary congestion does not seem to be a major finding in Chagas' cardiomyopathy (CC). This study sought to identify echocardiographic parameters associated with pulmonary congestion in CC and in dilated cardiomyopathy of other etiologies, such as non-CC (NCC), and to compare pulmonary venous hypertension between the two entities. METHODS: A total of 130 consecutive patients with CC and NCC, with similar echocardiographic characteristics, were assessed using Doppler echocardiography and chest radiography. Pulmonary venous vessel abnormalities were graded using a previously described pulmonary congestion score, and this score was compared with Doppler echocardiographic parameters. RESULTS: NCC patients were older than CC patients (62.4 ± 13.5 × 47.8 ± 11.2, p = 0.00), and there were more male subjects in the CC group (66.2% × 58.5%, p = 0.4). Pulmonary venous hypertension was present in 41 patients in the CC group (63.1%) and in 63 (96.9%) in the NCC group (p = 0.0), the mean lung congestion score being 3.2 ± 2.3 and 5.9 ± 2.6 (p = 0.0), respectively. On linear regression multivariate analysis, the E/e' ratio (β = 0.13; p = 0.0), LV diastolic diameter (β = 0.06; p = 0.06), left atrial diameter (β = 0.51; p = 0.08), and right ventricular (RV) end-diastolic diameter (β = 0.02; p = 0.48) were the variables that correlated with pulmonary congestion in both groups. CONCLUSIONS: Pulmonary congestion was less significant in patients with CC. The degree of LV of systolic and diastolic dysfunction and the RV diameter correlated with pulmonary congestion in both groups. The E/e' ratio was the hallmark of pulmonary congestion in both groups.